2011
DOI: 10.1176/appi.ajp.2011.11010148
|View full text |Cite
|
Sign up to set email alerts
|

Episodes of Mood Disorders in 2,252 Pregnancies and Postpartum Periods

Abstract: Among women with major affective disorders, illness risk was much greater during the postpartum period than during pregnancy. Illness mainly involved depression and was strongly associated with younger age at illness onset, bipolar disorder, and high lifetime occurrence rates. The relative risk during pregnancy compared with nonpregnant periods remains uncertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
188
1
8

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(208 citation statements)
references
References 41 publications
11
188
1
8
Order By: Relevance
“…An observational study of mood disorders in 2252 pregnancies and postpartum periods demonstrated that women with bipolar disorders were at particularly high risk of developing major depression in the postpartum period (prevalence: 19% and 29% in women with bipolar I disorder and bipolar II disorder, respectively). 62 Likewise, it has been shown that women with a history of psychotic disorder are at higher risk of postpartum psychiatric illness, in particular non-psychotic anxiety and depressive disorders. 63 The severity of these illnesses is highlighted by case reports of suicide among these women.…”
Section: Discontinuation and Factors Associated With Discontinuation mentioning
confidence: 99%
See 1 more Smart Citation
“…An observational study of mood disorders in 2252 pregnancies and postpartum periods demonstrated that women with bipolar disorders were at particularly high risk of developing major depression in the postpartum period (prevalence: 19% and 29% in women with bipolar I disorder and bipolar II disorder, respectively). 62 Likewise, it has been shown that women with a history of psychotic disorder are at higher risk of postpartum psychiatric illness, in particular non-psychotic anxiety and depressive disorders. 63 The severity of these illnesses is highlighted by case reports of suicide among these women.…”
Section: Discontinuation and Factors Associated With Discontinuation mentioning
confidence: 99%
“…As discussed in Discontinuation and factors associated with discontinuation of psychotropic medication in pregnancy previous research has demonstrated that both women with a psychotic disorder and women with mood disorders are at a particularly high risk of developing major depression and affective psychosis in the postpartum period. 62,63 Some observational studies have sought to compare the risks of relapse of mental illnesses during and after pregnancy in relation to psychotropic treatment. [65][66][67][68] Newport et al 65 observed 16 women who stopped lamotrigine treatment for bipolar disorder in pregnancy.…”
Section: Restarting and Factors Associated With Restarting Of Psychotmentioning
confidence: 99%
“…Certain populations have higher rates of PPD including 30% in women with a history of depression and 52% of women with bipolar disorder (Viguera et al, 2011). A growing body of evidence indicates that increased sensitivity to gonadal hormone levels such as estrogen mediate the biological vulnerability to PPD.…”
Section: Introductionmentioning
confidence: 99%
“…Women of childbearing age have been reported to be of particular risk, especially during the first postpartum year (Viguera et al, 2011;Yonkers et al, 2011). The prevalence of less severe forms of depression is less well known, but one study reported the presence of depressive symptoms in almost 40% of a sample of inner-city mothers (Heneghan, Silver, Bauman, Westbrook, & Stein, 1998).…”
mentioning
confidence: 99%